Relativity: photon - I. O. Sazonenko; V. I. Sapon (Литьë и металлургия, 2021)
For the case of interaction of polarized light with an analyzer (a polarizing device), an experimental scheme based on the Feynman idea of path integrals is proposed. Real and virtual photons are considered in the context of the Lenz rule (in terms of constructive and destructive induction). The Planck formula for the photon energy in the format of a verbal description is considered. The complexity of identifying the wave description of the photon with the ideas of the Ancient Greeks about elementary particles is shown. From the point of view of chronogeometry, it is shown that the stationary observer does not exist at the point of intersection of the cone of the past and the future, but in the time interval separating these regions. It is proposed to consider the fluctuations of the physical vacuum as a relic of the process of permanent inflation according to Linde. Based on the assumption of the self-measurement of the Universe, the quantum Zeno effect, and Hawking’s idea of the Universe being a quantum object with the Nth sum of Feynman stories, it is assumed that the history of the Universe is deterministic. From the perspective of the orthogonality of the electromagnetic field vectors E and B, the Heisenberg equation of the form Δp × Δx = ħ/2 is considered. A thought experiment is considered showing the complexity in describing the interaction of a photon with an electron of an atom from the point of view of the classical interaction of an electromagnetic wave with an antenna device. It is proposed to consider the absorption of a photon by an electron as its inertial collapse on an atom.